A Packing-Line Productivity Assessment of Particleboard Furniture - Tan, Jih Tsair (2003)
Malaysia, with its abundance of wood resources, is one of the traditional powerhouses of Asia's wood industry. In recent years, this sector has lost some of its edge simply because other countries have caught up, or have surpassed it in terms of competitiveness. Local manufacturers have no choice but to improve the production efficiency as well as the quality of their products if they want to remain competitive in the globalize market. In the production of panel particleboard furniture, the operations of packing department is more complicated and complex. The continuous packing process is affected by various factors, known and unknown, tangible and intangible. The objective of this paper is to study and analyze various factors contributing to the productivity of the packing line of particleboard furniture. The productivity and the frequency of the factors affecting the packing lines were measured and analyzed. The result showed that production planning, packing flow chart and work design (55%), insufficient of raw and supporting materials (21%), and the problems related to quality (14%) are the three most influencing factors to the productivity of packing lines, followed by insufficient of manpower arrangement (6%) and machinery breakdown (4%).